THE VIEW OF AHL AL-DZIMMAH THEORY REGARDING THE THOUGHTS OF THE INDONESIAN ULEMA COUNCIL (MUI) ABOUT POLICIES ON INTERFAITH SERVICES AT THE OFFICE OF RELIGIOUS AFFAIRS (KUA) - Siti Khoirotul Ula (LP3M IAI Al-Qolam, 2024)
This article discusses the stance of the Indonesian Ulema Council (MUI) regarding the Ministry of Religious Affairs' decision to transform Religious Affairs Offices (KUA) into service centres for all religions. The aim of this article is to analyse MUI's perspective on the policy related to religious services at KUA from the viewpoint of the ahlu dhimmah theory, a concept within the framework of Islamic governance. The research methodology employed in this article is qualitative research, relying on literature as the primary data source. Information for this study is drawn from the documents of the Eighth Ulama Fatwa Commission Meeting. The research findings indicate that, according to MUI, KUA should not be designated as a service centre for all religions in Indonesia. This decision is based on historical evidence showing that KUA, which operates under the Ministry of Religious Affairs, is specifically intended for Muslims as part of the compensation for the removal of seven words from the Jakarta Charter, which previously affirmed the obligation to uphold Islamic law for followers of Islam in Indonesia. The ideology that has replaced this is Pancasila. MUI also argues that issues related to religions other than Islam are significantly different from Islamic religious affairs, raising concerns about the potential for religious mixing if KUA becomes a service centre for all religions. MUI asserts that transforming KUA into a service centre for all religions contradicts existing laws and is not in line with the social realities of interfaith interactions. The implications of the analysis based on the ahlu dhimmah theory suggest that non-Muslims have the right to register marriages and receive implementation services at KUA. However, it is crucial that officials acting as